Memasyarakatkan Rebana sebagai Kesenian ala Islam-Nusantara - Wijaya, Bayu Tara (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
The issue of claiming the Nusantara of arts became the foundation of traditional art theme (Islamic art). Therefore, art has not been part of life intellectualism. Reality, art is still placed its function as a mere recreation, something to have fun for a moment. To that end, the Rebana Arts into one Nusantara arts result of cultural relevance to the era that originated from the acculturation of Islamic-Javanese culture has more benefits than trying to entertainment. Until now this has been growing rapidly with the development of science. Apparently, Rebana Art also have excess function, namely the spiritual aspects through chant blessings on to be one way to God. Hence the importance of socializing back Artistry Rebana with regard as Arts style Islamic-Nusantara.Because art tambourine is “spiritual treasures” that are not easily obtained from the other arts. Isu pengklaiman kesenian nusantara menjadi landasan dari pengangkatan tema kesenian tradisional (kesenian Islam). Sebab, kesenian belum menjadi bagian dari hidup kecendekiawanannya. Realitanya, kesenian masih diletakkan fungsinya sebagai rekreasi semata, sesuatu untuk bersenang-senang sesaat. Untuk itu, kesenian rebana menjadi salah satu kesenian Nusantara hasil dari relevansi budaya terhadap zaman yang berawal dari akulturasi budaya Islam-Jawa berusaha memiliki manfaat lebih sekadar hiburan. Hingga saat ini sudah berkembang pesat sesuai perkembangan ilmu pengetahuan. Ternyata, kesenian rebana pula memiliki kelebihan fungsi, yakni aspek spiritual melalui lantunan shalawat menjadi salah satu jalan menuju Tuhan. Maka pentingnya memasyarakatkan kembali kesenian rebana dengan menganggap sebagai kesenian ala Islam-Nusantara. Karena kesenian rebana adalah “harta karun spiritual” yang tidak mudah didapat dari kesenian lainnya.